Population Pharmacokinetics and Exposure‐Response Analyses to Guide Dosing of Icatibant in Pediatric Patients With Hereditary Angioedema. (22nd October 2020) - Wang, Yi; Jomphe, Claudia; Marier, Jean‐Francois; Martin, Patrick
Abstract: Elevated bradykinin levels are responsible for the development of clinical symptoms in patients with hereditary angioedema (HAE). Icatibant is a bradykinin type 2 receptor antagonist indicated for the acute treatment of HAE attacks. A population modeling and simulation approach was used to examine sources of variability impacting icatibant pharmacokinetics (PK) and provide guidance on icatibant dosing in pediatric patients with HAE. An exposure‐response analysis was performed for the time to onset of symptom relief (TOSR). Data from 141 adults (133 healthy, 8 with HAE) who received subcutaneous icatibant 30 mg and 31 pediatric patients with HAE who received 0.4 mg/kg (capped at 30 mg) were included in the analysis. Icatibant PK was described by a 2‐compartment model with linear elimination. Complete absorption of icatibant was expected within 1 hour of dosing. The apparent clearance and central volume of distribution were 15.4 L/h and 20.4 L, respectively. Icatibant PK was mainly dependent on body weight. The mean TOSR was very short (1.38 hours). A flat exposure‐response was observed, confirming that the relationship plateaued at the level of exposure observed in pediatric patients. Simulations confirmed that weight band–based dosing regimens (10 mg [12‐25 kg], 15 mg [26‐40 kg], 20 mg [41‐50 kg], 25 mg [51‐65 kg], and 30 mg [>65 kg]) resulted in exposure similar to the 0.4‐mg/kg dose. This analysis showed that icatibant undergoes rapid absorption, reaches levels required for therapeutic response, and promptly relieves HAE symptoms. A weight band–based dosing regimen is appropriate in pediatric patients with HAE.